Dry-land strength and conditioning for prepubertal and peripubertal swimmers - Amaro, Nuno (2020)
Swimming success depends on several factors. The ability to apply in-water force is crucial, particularly in short distances (13,15). Among others methodologies, dry-land strength and conditioning training is a common practice in competitive swimming. [...]